Naszym wzorem chłopi-patrioci, przodownicy w realizacji zobowiązań wsi wobec Państwa! (Gdańsk : [s.n.], 1951)
Plakat propagandowy.
Keywords: Wsie -- Polska -- 1945-1970 -- plakaty; Propaganda -- Polska -- 1945-1970 -- plakaty